2011
DOI: 10.1111/j.1365-2036.2011.04902.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: comparative study of 10‐day sequential therapy with 7‐day standard triple therapy for Helicobacter pylori infection in naïve patients

Abstract: SUMMARY BackgroundThe eradication rates following standard triple therapy for Helicobacter pylori infection are declining worldwide. Recent studies have shown that sequential therapy for H. pylori infection yields high cure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 50 publications
4
40
0
Order By: Relevance
“…In Korea, a study compared the eradication rate of the 10-day sequential therapy with that of the 14-day standard therapy and found a significantly higher rate of eradication in the sequential group (92.6 vs 85%) with no difference in adverse events [11]. Two other studies from Korea compared sequential therapy to a 7-day standard regime and also showed superior eradication in favor of sequential therapy [12,13]. In Taiwan, sequential therapy was also superior to standard triple therapy (93 vs 80%) with similar rates of adverse events and compliance [14].…”
Section: Triple Therapymentioning
confidence: 99%
“…In Korea, a study compared the eradication rate of the 10-day sequential therapy with that of the 14-day standard therapy and found a significantly higher rate of eradication in the sequential group (92.6 vs 85%) with no difference in adverse events [11]. Two other studies from Korea compared sequential therapy to a 7-day standard regime and also showed superior eradication in favor of sequential therapy [12,13]. In Taiwan, sequential therapy was also superior to standard triple therapy (93 vs 80%) with similar rates of adverse events and compliance [14].…”
Section: Triple Therapymentioning
confidence: 99%
“…8,9 These results were attributed to the increased resistance of H. pylori to antibiotics, especially clarithromycin and metronidazole, in our province. In the 1990s, a high-dose proton pump inhibitor (PPI)-amoxicillin dual therapy was introduced as one of the alternative first-line therapies based on the theoretical studies showing that amoxicillin has a lower incidence of resistance compared with clarithromycin or metronidazole, and that its bactericidal effect can be amplified by increasing the maximum intragastric pH using high-dose PPI.…”
Section: Introductionmentioning
confidence: 92%
“…However, more recent studies have questioned both the optimal performance rates and the superiority of sequential therapy compared to legacy triple therapy [37,38] . Indeed, a recent multicenter South American randomized trial demonstrated that 14-d standard triple therapy was more efficacious than the 10-d sequential regimen [17] .…”
Section: Standard Sequential Therapymentioning
confidence: 98%